HOSPITAL FOOD SERVICE ASSESSMENT IMPROVING NUTRITIONAL INTAKE INPATIENTS: A LITERATURE REVIEW - Ria Qadariah Arief; Linda Prasetyaning Widayanti; Sri Hidayanti; Sarita Oktorina; Maryam Jamila Arief; Syamsul Alam (Homes Journal = Hospital Management Studies Journal, 2023)
Background: Malnutrition in hospitals is a commonly occurring and often overlooked issue that impacts not only the clinical outcomes of patients, such as their length of stay, morbidity, mortality, and quality of life, but also the overall sustainability of the healthcare system. column format. Aims: The purpose of writing this systematic literature review is to collect scientific evidence regarding food service satisfaction assessment techniques for inpatients in hospitals. Method: This research conducting a literature review using PRISMA guidelines, using data based on Google Scholar and Scopus which examined the level of patient satisfaction with food services in hospitals. Result: From the six papers that we analyzed, we obtained an assessment process for the level of patient satisfaction using caloric intake calculations, and some used validated questionnaires, and obtained several appropriate strategies to increase the nutritional intake of inpatients. Conclusions: Assessing the patient's nutritional and nutritional intake is very important in determining the patient's health and recovery.